1997
DOI: 10.1002/elan.1140090406
|View full text |Cite
|
Sign up to set email alerts
|

Disposable multichannel immunosensors for 2,4‐dichlorophenoxyacetic acid using acetylcholinesterase as an enzyme label

Abstract: An improved version of the disposable multichannel immunochemical biosensor for the herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) based on a screen-printed amperometric transducer and monoclonal antibodies (MAb) against 2,4-D is reported. Entrapment within a thin Nafion film was used for the direct immobilization of MAb at the electrode surface. The amount of the tracer (2,4-D conjugated to acetylcholinesterase) bound in a competitive immunochemical reaction was determined amperometrically using acetylthioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

1998
1998
2003
2003

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 34 publications
0
17
0
2
Order By: Relevance
“…Further improvement is desired such as the development of compact, user-friendly, hand-held multichannel device (35), or the miniaturization of the sensor (i.e., microelectrodes) with the aim of working in smaller assay volumes for increasing the sensitivity. We have recently shown that a monolayer of biotin can be electrochemically grafted on the surface of carbonbased SPE, thus offering new opportunity for the immobilization of oligonucleotides on small electrode surfaces (36).…”
Section: Resultsmentioning
confidence: 99%
“…Further improvement is desired such as the development of compact, user-friendly, hand-held multichannel device (35), or the miniaturization of the sensor (i.e., microelectrodes) with the aim of working in smaller assay volumes for increasing the sensitivity. We have recently shown that a monolayer of biotin can be electrochemically grafted on the surface of carbonbased SPE, thus offering new opportunity for the immobilization of oligonucleotides on small electrode surfaces (36).…”
Section: Resultsmentioning
confidence: 99%
“…Faixas de detecção na ordem de 10 -7 a 10 -11 mol L -1 foram obtidas. Essa mesma classe de enzimas foi explorada na construção de um imunossensor descartável 55 , do tipo multicanal, usando um anticorpo monoclonal e um conjugado 2,4-DAChE. O método mostrou-se sensível na ordem de partes por milhão, e foi aplicado à análise de amostras de água.…”
Section: Análise Do 24-dunclassified
“…Acetilcolinesterase (AchE): emprega a acetiltiocolina como substrato e a determinação do analito ocorre monitorando a tiocolina 37 ; tem sido usada como enzima marcadora de reação imunoenzimática, uma vez que exibe uma alta constante catalítica 38 ; a presença de grupos amino primário permite o uso da AchE no acoplamento de haptenos sem alterar as propriedades catalíticas da enzima 39 .…”
Section: Enzima Marcadoraunclassified